PANDANGAN DAN OPINI MENGENAI KEBERADAAN HUKUM ADAT DALAM KAITANNYA DENGAN LAND REFORM DI INDONESIA - Achmad Khairi (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Adat law in Indonesia cannot be denied its existence. This is because adat law has existed from generation to generation since ancestral times before the Indonesian state de jure and de facto existed. But then the problem arises when the state is formed and adat law is